Effect of fragaria vesca, hamamelis and tormentil on the initial bacterial colonization in situ - Kirsch, Jasmin; Jung, Amira; Hille, Kristin; König, Belinda; Hannig, Christian; Kölling-Speer, Isabelle; Speer, Karl; Hannig, Matthias (Archives of Oral Biology, 2020)
•Fragaria vesca, hamamelis and tormentil significantly reduce initial bioadhesion and glucan formation in situ.•Fragaria vesca, hamamelis and tormentil lead to a thicker more electron dense pellicle.•Fragaria vesca, hamamelis and tormentil and are recommended as adjuvant antibacterial oral therapeutics. The presentin situ study aims to examine the influence of the polyphenolic tea drugs fragaria vesca, hamamelis and tormentil on the initial oral bioadhesion. Initial biofilm formation was performed on bovine enamel slabs which were carried intraorally by 12 subjects. After 1 min of intraoral pellicle formation, the subjects rinsed with fragaria vesca, tormentil (0.8 mg/8 mL) and hamamelis (0.2 mg/8 mL) for 10 min. Tap water served as negative control, 0.2 % CHX as positive control. The investigations took place on different days (wash-out: 2 days). Afterwards, fluorescence microscopy has been performed per test solution (n = 5) and per subject (n = 12) to visualize bacterial adhesion and glucan formation (8 h oral exposition) with DAPI, ConA and BacLight. Additionally, TEM was used to visualize the pellicle ultrastructure and expectorate samples. Statistical evaluation was carried out using the Kruskal-Wallis- (p < 0.5), Mann–Whitney U test (p < 0.5) and Bonferroni-Holm-correction (p < 0.1). Rinsing with the polyphenolic tea extracts reduced significantly initial bacterial colonization (DAPI) compared to the negative control. There was no significant difference betweenfragaria vesca, hamamelis and tormentil. All solutions showed a reducing effect on the glucan formation. No significant difference was observed between fragaria vesca and CHX. Considerable alterations of the pellicle’s ultrastructure manifested by an increase in thickness and electron density resulted from rinsing with the three polyphenolic aqueous extracts. Fragaria vesca, hamamelis and tormentil significantly reduce initial bioadhesion and glucan formation in situ and are therefore recommended as adjuvant antibacterial oral therapeutics.